The Role Of Religiosity And Family Involvement In The Sustainability Of Citrus Farming In Sukopura Village, Jabung District, Malang Regency (A Case Study) - Wicaksono, Arif; Sudarmiatin; Puji Handayati; Naswan Harsono (Citakonsultindo, 2025)
The sustainability of citrus farming in Sukopuro Village, Malang Regency, faces serious challenges in the form of declining interest among the younger generation, pest and disease attacks, and unpredictable climate change. Amidst these conditions, religious values and family involvement are believed to play an important role in maintaining farmers' resilience and business continuity. This study aims to analyze how religiousness and family involvement shape the practice of sustainable citrus farming. The study uses a qualitative approach with a case study design, involving farmers, family members, and religious leaders as informants. Data were collected through in-depth interviews, observations, and documentation, then analyzed using the Miles, Huberman, and Saldaña technique. The results show that religiosity functions as spiritual capital that increases farmers' psychological resilience in facing production uncertainty, while family involvement becomes a social foundation that strengthens the inheritance of values, division of roles, and business continuity between generations. However, the challenges of regeneration, climate risks, and ecological vulnerability remain major obstacles to maintaining business sustainability. This study concludes that the sustainability of the citrus business is not only determined by technical factors but also depends heavily on the strength of religious-social capital and family solidarity. These findings make an important contribution to strengthening the sustainability model of agriculture based on local values and family culture